2014
DOI: 10.1159/000358395
|View full text |Cite
|
Sign up to set email alerts
|

Lateralization of Ovarian Follicles

Abstract: Background/Aim: To evaluate a possible lateralization of antral follicle count (AFC) based on the finding that endometriosis, if present, is more commonly found in the left hemipelvis. Methods: We evaluated the records of 6,617 baseline ultrasounds conducted at our Reproductive Center between 2007 and 2011 in a university teaching hospital setting. We included all ultrasounds with an AFC of 1 or greater and excluded those with incomplete documentation or with ovarian cyst, including endometriotic cysts (n = 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…We noted that the right ovary contained more follicles than the left ovary in women with PCOS, consistent with the greater volume of the right ovary. Our findings are similar to those of some (26,27,29,30), but not all (31), previous studies of right-left differences in FNPO in women with infertility or PCOS, where the investigators (26,27,29,30) have reported 0.1-2.0 more follicles in the right ovary. Our higher result of five follicles could reflect our unique approach to offline image analysis (24) compared with other investigators' real-time (27,(29)(30)(31) or semiautomated counts (26).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We noted that the right ovary contained more follicles than the left ovary in women with PCOS, consistent with the greater volume of the right ovary. Our findings are similar to those of some (26,27,29,30), but not all (31), previous studies of right-left differences in FNPO in women with infertility or PCOS, where the investigators (26,27,29,30) have reported 0.1-2.0 more follicles in the right ovary. Our higher result of five follicles could reflect our unique approach to offline image analysis (24) compared with other investigators' real-time (27,(29)(30)(31) or semiautomated counts (26).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are similar to those of some (26,27,29,30), but not all (31), previous studies of right-left differences in FNPO in women with infertility or PCOS, where the investigators (26,27,29,30) have reported 0.1-2.0 more follicles in the right ovary. Our higher result of five follicles could reflect our unique approach to offline image analysis (24) compared with other investigators' real-time (27,(29)(30)(31) or semiautomated counts (26). There are some challenges associated with the assessment of FNPO, including distinguishing an anechoic structure as one or two clustered follicles and recounting follicles that have already been flagged.…”
Section: Discussionsupporting
confidence: 92%
“…Alserri et al conducted a retrospective observational study using a large sample of 6617 ultrasound scans, to assess a potential association of AFC with laterality [ 35 ]. The findings supported that antral follicular counts are significantly higher in the right side, compared to the left.…”
Section: Discussionmentioning
confidence: 99%
“…The findings supported that antral follicular counts are significantly higher in the right side, compared to the left. This association was prevalent both in patients with polycystic ovarian morphology (PCO) and controls, when ovarian reserve was considered normal based on AFC counts [ 35 ]. Interestingly, the significant difference was eliminated in the subgroup of women with low ovarian reserve, as classified by an AFC count between 1 and 9 [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian reserve can be evaluated using multiple tools such as basal FSH and LH concentrations, AMH level, estradiol concentration, total AFC, and OV [13,14]. Other tests include ovarian biopsy or dynamic endocrine tests such as the clomiphene citrate challenge test and the gonadotropin-releasing hormone stimulation test [7].…”
Section: Discussionmentioning
confidence: 99%